Complementary Metal Oxide Semiconductor - Ho Yeap, Kim; Nisar, Humaira (IntechOpen, 2018)
In this book, Complementary Metal Oxide Semiconductor ( CMOS ) devices are extensively discussed. The topics encompass the technology advancement in the fabrication process of metal oxide semiconductor field effect transistors or MOSFETs (which are the fundamental building blocks of CMOS devices) and the applications of transistors in the present and future eras. The book is intended to provide information on the latest technology development of CMOS to researchers, physicists, as well as engineers working in the field of semiconductor transistor manufacturing and design.